2019
DOI: 10.1111/jofo.12279
|View full text |Cite
|
Sign up to set email alerts
|

Use of autonomous audio recordings for the rapid inventory of birds in the white-sand forests of the Peruvian Amazon

Abstract: White‐sand forests are patchily distributed ecosystems covering just 5% of Amazonia that host many specialist species of birds not found elsewhere, and these forests are threatened due to their small size and human exploitation of sand for construction projects. As a result, many species of birds that are white‐sand specialists are at risk of extinction, and immediate conservation action is paramount for their survival. Our objective was to evaluate current survey methods and determine the relative effect of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“… Leach et al (2016) sampled birds in a rainforest in Queensland and found that point counts led to greater estimations of species richness because of additional species detected visually. Similarly, Stevens et al (2019) found that point counts were more useful for canopy passerines in white-sand forests of Amazonia. On the other hand, Alquezar & Machado (2015) found that the two methods gave similar results in cerrado vegetation with visual detections at point counts not contributing additional species.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… Leach et al (2016) sampled birds in a rainforest in Queensland and found that point counts led to greater estimations of species richness because of additional species detected visually. Similarly, Stevens et al (2019) found that point counts were more useful for canopy passerines in white-sand forests of Amazonia. On the other hand, Alquezar & Machado (2015) found that the two methods gave similar results in cerrado vegetation with visual detections at point counts not contributing additional species.…”
Section: Discussionmentioning
confidence: 89%
“…Acoustic monitors have proven to be useful for sampling bird species in a variety of habitats, including both temperate ( Celis-Murillo, Deppe & Allen, 2009 ; Depraetere et al, 2011 ; Cook & Hartley, 2018 ) and tropical ( Bueno et al, 2012 ; De Camargo, Roslin & Ovaskainen, 2019 ; Stevens et al, 2019 ) forests. They have been used to provide descriptions of bird species richness, community composition, and change in such communities over space and time ( Towsey et al, 2014 ; De Camargo, Roslin & Ovaskainen, 2019 ; Stevens et al, 2019 ). Recordings from acoustic monitors also have been used to develop acoustic indices that provide information on diversity, without identification of individual species ( Depraetere et al, 2011 ; Towsey et al, 2014 ; Aide et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…2014). Stevens et al . (2019) used ARUs at heights of 2-5m and documented decreased detection rates of canopy-dwelling mixed flock species relative to point counts, but found no such effects in habitats with shorter, smaller trees, supporting the idea that the distance between recorder and canopy height meaningfully influences detection rates of canopy species.…”
Section: Discussionmentioning
confidence: 99%
“…The system can be therefore considered as simple, efficient and accessible to non-experts. Several studies have shown that similar PAM systems can be as informative as point count sampling technique traditionally used in conservation programs (Haselmayer and Quinn, 2012;Shonfield and Bayne, 2017;Stevens et al, 2019).…”
Section: Discussionmentioning
confidence: 99%